2007
DOI: 10.1111/j.1471-4159.2006.04376.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor‐γ agonists induce neuroprotection following transient focal ischemia in normotensive, normoglycemic as well as hypertensive and type‐2 diabetic rodents

Abstract: Thiazolidinediones (TZDs) are synthetic agonists of the ligand-activated transcription factor peroxisome proliferatoractivated receptor-c (PPARc). TZDs are known to curtail inflammation associated with peripheral organ ischemia. As inflammation precipitates the neuronal death after stroke, we tested the efficacy of TZDs in preventing brain damage following transient middle cerebral artery occlusion (MCAO) in adult rodents. As hypertension and diabetes complicate the stroke outcome, we also evaluated the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
220
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(234 citation statements)
references
References 58 publications
(73 reference statements)
11
220
0
3
Order By: Relevance
“…These findings strongly suggest that the upregulation of 5-LO induced by rosiglitazone is beneficial and mediates the neuroprotective effect of rosiglitazone after MCAO. Anti-inflammatory mechanisms have been demonstrated to mediate the neuroprotective effects of PPAR␥ agonists (Pereira et al, 2005(Pereira et al, , 2006Sundararajan et al, 2005;Zhao et al, 2005;Collino et al, 2006;Luo et al, 2006;Zhao Y et al, 2006;Tureyen et al, 2007). Our present data confirm this mechanism of rosiglitazone, as shown by the inhibition of the expression of inflammatory genes with a deleterious role in cerebral ischemia, namely, COX-2, iNOS, MMP9 and TNF-␣.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings strongly suggest that the upregulation of 5-LO induced by rosiglitazone is beneficial and mediates the neuroprotective effect of rosiglitazone after MCAO. Anti-inflammatory mechanisms have been demonstrated to mediate the neuroprotective effects of PPAR␥ agonists (Pereira et al, 2005(Pereira et al, , 2006Sundararajan et al, 2005;Zhao et al, 2005;Collino et al, 2006;Luo et al, 2006;Zhao Y et al, 2006;Tureyen et al, 2007). Our present data confirm this mechanism of rosiglitazone, as shown by the inhibition of the expression of inflammatory genes with a deleterious role in cerebral ischemia, namely, COX-2, iNOS, MMP9 and TNF-␣.…”
Section: Discussionsupporting
confidence: 79%
“…Our results show that 1) rosiglitazone-induced 5-LO expression and subsequent lipoxin synthesis mediate most of the neuroprotective effects of rosiglitazone in experimental stroke as well as its late PPAR␥ agonistic effect and 2) that LXA 4 is neuroprotective by acting, at least partly, as a PPAR␥ agonist. Several groups have previously reported that PPAR␥ agonists are neuroprotective in brain ischemia (Pereira et al, 2005(Pereira et al, , 2006 Tureyen et al, 2007), due mainly to anti-inflammatory and anti-oxidant mechanisms; anti-excitotoxic actions could also be involved, either at the presynaptic level (Romera et al, 2007) or postsynaptically (X. . Intriguingly, using cDNA microarray analysis, we found a robust expression of 5-LO mRNA after rosiglitazone administration, concomitant to neuroprotection (Pereira et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the synthetic ligands of PPAR-gamma, rosiglitazone and pioglitazone, which belong to the TZD class of agonists, have been approved by the FDA to treat type-II diabetes mellitus. Diabetic patients face an increased propensity to suffer a stroke, and stroke inflicts significantly more damage in diabetic and hypertensive patients than in normoglycemic and/or normotensive individuals (32,33,101). It was first observed that the PPAR-alpha and the PPAR-gamma agonists protect against stroke and that this beneficial outcome is associated with improved endothelial relaxation, reduced oxidative stress and decreased VCAM1 and ICAM1 expression (26,101,104).…”
mentioning
confidence: 99%
“…Huang et al (28) demonstrated that IL-4 induces the generation of endogenous ligands for PPAR-gamma by activating the 12/15-lipoxygenase pathway in macrophages, suggesting an IL-4-mediated down-regulation of iNOS expression. These studies suggested that PPAR-gamma agonists might mediate anti-inflammatory effects through PPAR-gamma-independent mechanisms as well.A novel mechanism for the PPAR-gamma-independent anti-inflammatory actions of TZDs, is the involvement of the Janus kinase (JAK) and the STAT signaling pathways (33,67,68). Transphosphorylation of the cytokine receptor-associated JAK leads to its dimerization and phosphorylation of the downstream STATs.…”
mentioning
confidence: 99%
“…It was proven that PPAR-γ has a dramatically positive effect on infarct size, HT rate and neurological outcome. The underlying mechanism is assumed to be the decreased expression of inflammatory mediators, such as IL-1, cyclooxygenase-2, inducible nitric oxide synthase [230]. Further mechanisms of suppressing the inflammatory response are involved as well [231].…”
Section: Roziglitazonementioning
confidence: 99%